2017
DOI: 10.1002/app.45061
|View full text |Cite
|
Sign up to set email alerts
|

New polyurea MWCNTs nanocomposite films with enhanced mechanical properties

Abstract: Polyurea nanocomposites represent a promising option in the development of advanced materials for applications that require high mechanical resistance. This article describes an optimized synthetic route for obtaining polyurea nanocomposites with enhanced mechanical properties by employing epoxy‐functionalized multiwalled carbon nanotubes (MWCNTs) as reinforcing agent. The experimental measurements revealed that these functionalized nanofillers have a positive effect on the properties of the composite only unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…It is known that the two main factors such as dispersion of carbon nanomaterials and interfacial interaction of nanomaterials and polymer matrix govern the mechanical properties of the nanocomposite . In this study, the vast improvement in mechanical properties of PUs using MWCNTs agreed with the literatures . Qian et al showed an 80% improvement in tensile strength by adding 0.2 wt% of graphene from 13 to 23.6 MPa, whereas a 71% improvement in Young's modulus was presented in MWCNTs/PU composite by Toader et al at the same concentration.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…It is known that the two main factors such as dispersion of carbon nanomaterials and interfacial interaction of nanomaterials and polymer matrix govern the mechanical properties of the nanocomposite . In this study, the vast improvement in mechanical properties of PUs using MWCNTs agreed with the literatures . Qian et al showed an 80% improvement in tensile strength by adding 0.2 wt% of graphene from 13 to 23.6 MPa, whereas a 71% improvement in Young's modulus was presented in MWCNTs/PU composite by Toader et al at the same concentration.…”
Section: Resultssupporting
confidence: 87%
“…Indeed, the MWCNT doping has caused a 5.5 C increase in the decomposition onset temperature which is an indication of increased thermal stability. Toader et al [26] who conducted a similar MWCNT doping of an aromatic PU experienced a similar TGA result reporting that the addition of MWCNTs offered a small but positive impact on the thermal stability of PU. Figure 6 shows the DSC heat flow diagram of both samples.…”
Section: Thermal and Chemical Propertiesmentioning
confidence: 73%
See 1 more Smart Citation
“…In order to confirm the chemical modification of the CNF, XPS analysis was performed on the two modified CNF. The XPS analysis (Figure ), C1s deconvolution, for the modified CNF confirmed the chemical modification, which is sustained by the change of the C‐C sp 2 percentage and increase in C‐C sp 3 . Also, in the case of AA functionalization, oxygen content of the modified CNF was determined to be 11.95% (atomic %), whereas the in the case of GMA 15.85% (atomic %).…”
Section: Resultsmentioning
confidence: 58%
“…The XPS analysis (Figure 2), C1s deconvolution, for the modified CNF confirmed the chemical modification, which is sustained by the change of the C-C sp 2 percentage and increase in C-C sp 3 . [18][19][20] Also, in the case of AA functionalization, oxygen content of the modified CNF was determined to be 11.95% (atomic %), whereas the in the case of GMA 15.85% (atomic %). This difference is due to the different oxygen content of the monomers as well as to their different reactivity in radical polymerization.…”
Section: Resultsmentioning
confidence: 98%